Mothers’ Knowledge Toward Oral Health of Children Under 5 Years Old - Fatimah Assad Jumaa, Salwa Ghazi Turki, Khatam Mutasher Hattab (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Poor oral hygiene may have a mainly effect on body health in general. Childhood is an important period of life that needs to be monitored closely so that the child will grow up healthy. As a child spends majority of time with his mother, she has the key role in his healthy and proper developing. The mother’s knowledges, towards the oral health care of their children acts as a significant predictor of the child’s health. Objective(s): This study aimed to evaluate mothers’ knowledge toward oral health of children under 5 years old. Methodology: A descriptive study design carried out between October 27th, 2021 to march 30th 2022 on mothers of children under 5 years at primary dental health care, to evaluate the mother knowledge about oral health. The research sample includes (310) mothers of children under five years old. They are selected by using non-probability sampling (convenience sample). Results: Results shows that "Stages of tooth development and growth" observed that most of the mothers respondents had responded at a high level evaluating and assigned 4 (57.14%) items with a moderate, and 3(42.86%) items with a high levels, then followed by the second sub domain of "Role of Fluoride in Dental Health" had a moderate evaluating for 5(80.0%) items, while leftover item are assigned a high evaluation level, the third sub domain of "Children’s Diet and Oral Hygiene" had a high evaluating for 3(42.86%) items, while it came to evaluate moderate for two items, and the other two were assigned at low levels. Finally, the fourth subdomain "Problems and Diseases of Teeth and Gums among Children" revealed that mothers’ respondents had responded at a moderate level evaluating 6(42.86%) items, and with a high level 5(35.71%) items, while leftover items of low level are accounted 3(21.43%). Conclusion: Mothers knowledge’s items regarding Children’s Oral Health has a evaluate at a moderate level generally assigned somewhat away from the target in which that achieving the goal of this study. Recommendation: Encourage mothers to regular visit to dentist clinic and assess the children oral cavity and identify any health problems .Teach child to brush with fluoride toothpaste after eating or drinking any meal. Reduce eating sweeting and chocolate meals and make sure to brush teeth after eating them. Improving and providing health services in primary health care dental services.